Very High-dose Cholecalciferol and Arteriovenous Fistula Maturation in ESRD: A Randomized, Double-blind, Placebo-Controlled Pilot Study. Issue 2 (March 2014) - Wasse, Haimanot; Huang, Rong; Long, Qi; Zhao, Yize; Singapuri, Salman; McKinnon, William; Skardasis, George; Tangpricha, Vin
Purpose: While vitamin D is critical for optimal skeletal health, it also appears to play a significant role in vascular homeostasis. This pilot study compared arteriovenous (AV) access outcomes following cholecalciferol supplementation compared to placebo in end-stage renal disease patients preparing to undergo AV access creation. Methods: A total of 52 adult hemodialysis patients preparing for arteriovenous fistula (AVF) creation were randomized to receive perioperative high-dose cholecalciferol versus placebo in this double-blind, randomized, placebo-controlled pilot study. The primary outcome was mean response to high-dose oral cholecalciferol versus placebo, and secondary outcome AV access maturation at 6 months. Logistic regression was used to assess the association between AV access maturation and baseline, posttreatment and overall change in vitamin D concentration. Results: A total of 45% of cholecalciferol-treated and 54% of placebo-treated patients were successfully using their AVF or arteriovenous graft (AVG) at 6 months (p=0.8). Baseline serum concentrations of 25(OH)D and 1, 25(OH)2 D did not differ between those who experienced AVF or AVG maturation and those who did not (p=0.22 and 0.59, respectively). Similarly, there was no relationship between AVF or AVG maturation and posttreatment serum 25(OH)D and 1, 25(OH)2 D concentration (p=0.24 and 0.51, respectively). Conclusions: Perioperative high-dose vitamin D3 therapy does correct 25(OH)D level but does not appear to have an association with AV access maturation rates. Future research may include extended preoperative vitamin D3 therapy in a larger population or in certain subpopulations at high risk for AVF failure.